Analysis of Potassium Levels in Patients with Pulmonary Tuberculosis Who Take Anti Tuberculosis Drugs - Laila Kamilla; Qorina Miranti; Linda Triana; Sri Tumpuk (Jurnal teknologi Kesehatan Borneo, 2023)
Pulmonary Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis. Pulmonary Tuberculosis is treated with antituberculosis drugs, but these drugs can be toxic to the body and have side effects such as diarrhea, nausea, and vomiting. These side effects can disrupt the body's fluid balance with the loss of potassium. The purpose of this study was to analyze the side effects of taking anti-tuberculosis drugs (OAT) on potassium (K) electrolyte levels in Pulmonary Tuberculosis patients at UPT Puskesmas Perumnas 1. This study used a descriptive design with a cross sectional approach to describe or give an overview of electrolyte levels in Pulmonary Tuberculosis patients who took anti-tuberculosis drugs. The population in this study were 37 Pulmonary Tuberculosis patients, and the samples in this study were 26 Pulmonary Tuberculosis patients who were still on OAT treatment at UPT Puskesmas Perumnas 1. The potassium electrolyte examination method used in this study was the sodium tetraphenylboron method. From the results of the study, it was found that Lung Tuberculosis patients with normal potassium levels amounted to 8 people (30.8%) and Lung Tuberculosis patients who experienced hypokalemia amounted to 18 people (69.2%). The side effects felt from taking OAT were digestive disorders, namely diarrhea totaling 7 people (26.9%), nausea totaling 4 people (15.4%), and vomiting totaling 7 people (26.9%).